PENGARUH KARAKTER KEWIRAUSAHAAN, DIGITAL MARKETING DAN E-COMMERCE TERHADAP PENINGKATAN KINERJA PEMASARAN UMKM SEKTOR KULINER DI BULELENG - Kadek, Kadek Agus Hendriawan; Trianasari; Telagawati , Ni Luh Wayan Sayang (Jurnal Magister Manajemen, 2024)
This research aims to analyze the influence of entrepreneurial character, the use of digital marketing and e-commerce on improving marketing performance in Micro, Small and Medium Enterprises (MSMEs) in the culinary sector in Buleleng Regency. The research method used was a survey by distributing questionnaires to owners of culinary MSMEs operating in the area. The collected data was analyzed using statistical regression techniques to determine the relationship and impact of the variables studied. It is hoped that the results of this research will provide a deeper understanding of the role of entrepreneurial character, digital marketing and e-commerce in improving the marketing performance of culinary MSMEs in Buleleng. The practical implications of the findings of this research can provide guidance for business actors to optimize their entrepreneurial character, increase the use of digital marketing, and integrate e-commerce as a strategy to improve marketing performance. It is hoped that the results of this research can become the basis for government policies and strategies for developing MSMEs in the culinary sector to encourage local economic growth